2008
DOI: 10.1097/mlr.0b013e31816080fe
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Predictors of Undetected Eye Disease in Mexican-Americans

Abstract: Background-Latinos have one of the highest rates of visual impairment associated with eye disease in the United States. Although little is known about the prevalence and risk of undetected eye disease (UED) in this population, it is known that Latinos encounter disproportionate barriers in accessing health care, which may influence the burden of UED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 32 publications
2
47
0
2
Order By: Relevance
“…584,[586][587][588] Recent immigration 582,583 has been identified as a risk factor for vision loss, the most common cause of which is uncorrected refractive error. 582,585,589 The prevalence of vision loss (< 6/15) due to uncorrected refractive error is estimated at 5.4% for those 12 and older in the general population and substantially higher in minority populations.…”
Section: Vision Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…584,[586][587][588] Recent immigration 582,583 has been identified as a risk factor for vision loss, the most common cause of which is uncorrected refractive error. 582,585,589 The prevalence of vision loss (< 6/15) due to uncorrected refractive error is estimated at 5.4% for those 12 and older in the general population and substantially higher in minority populations.…”
Section: Vision Healthmentioning
confidence: 99%
“…581 Similar global disparities in access to care are anticipated for other common causes of vision loss. 579 In the United States, minority populations have higher levels of vision loss and undiagnosed eye disease [582][583][584][585] than does the general population. Numerous factors contribute to this disparity, including socioeconomic status, access to care, societal conventions, and physiologic and anatomic differences.…”
Section: What Is the Burden Of Vision Loss In Immigrant Populations?mentioning
confidence: 99%
“…(1) blurring of vision, (2) cataract formation, (3) diabetic pupil, (4) diabetic retinopathy, (5) macular edema, (6) retinal neovascularization, (7) vitreous hemorrhage, (8) retinal detachment, (9) neovascularization of the iris (i.e. Rubeosis iridis), (10) cranial nerveCN III, IV and VI palsy.…”
Section: Ophthalmic Featuresmentioning
confidence: 99%
“…Cataract formation is a common cause of vision loss in diabetic patients [8]. It is estimated that diabetics have a 60% increased risk of developing cataracts [9].…”
Section: Ophthalmic Featuresmentioning
confidence: 99%
“…In East Baltimore, a 1994 study with 405 general medicine patients over the age of 40 of whom 94% were black showed that 50.6% of patients had clinically important ocular pathology and one third of those were unaware of the disease [3]. A study of 6,357 Latinos showed 53% of subjects had eye disease and of those, 63% had undetected eye disease [4]. One method of early detection is to screen elderly individuals for early signs of retinal diseases [5].…”
Section: Introductionmentioning
confidence: 99%